First report of the emerging pathogenic yeast Candida palmioleophila in commercially relevant fish from southeastern Brazil - Oliveira, Manoel M. E.; Lima, Viviane Felix Moraes; Costa, Gisela Lara da; Baptista, Barbara de Oliveira; Augusto, Julia Auad; Hauser-Davis, Rachel Ann (Frontiers in Fungal Biology, 2025)
The emerging fungal pathogen Candida palmioleophila (C. palmioleophila) has been increasingly detected in environmental and animal samples, although studies in this regard are still scarce, especially in fisheries contexts. This study reports the first-time detection of C. palmioleophila in a commercially relevant fish species belonging to the Sciaenidae family (Cynoscion sp.), indicating its potential emergence as a pathogen in Brazil. We applied CHROMagar Candida Plus medium identification associated to Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) for the identification of C. palmioleophila isolates. Although only one fish specimen was shown to be contaminated by C. palmioleophila, this study provides the first evidence of this yeast circulating in commercially relevant fish species in Brazil, highlighting the potential risks associated with this emerging pathogen.